Answer

Verified

372.3k+ views

**Hint:**In order to solve this question, we need to use the half angle formula to find the respective values of the trigonometric functions. We find the value of $x$ by equating $\dfrac{x}{2}$ with $\dfrac{\pi }{{12}}$. We place this value in the half angle formula and solve it further to get our required answers.

**Formula used:**${\sin ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \cos x}}{2}$,${\cos ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 + \cos x}}{2}$,${\tan ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \cos x}}{{1 + \cos x}}$

**Complete Step by Step Solution:**

In this question, we are asked to find the values of the trigonometric functions sine, cosine and tangent for the angle $\dfrac{\pi }{{12}}$ using the half angle formula.

All values less than $\dfrac{\pi }{2}$ fall in the first quadrant of a trigonometry unit circle.

As all the trigonometric functions are positive in the first quadrant hence the trigonometric functions for the angle $\dfrac{\pi }{{12}}$ will also be positive as it falls in the first quadrant.

The half angle formula for sine is given as:

$ \Rightarrow {\sin ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \cos x}}{2}$

Angle $\dfrac{x}{2}$ here corresponds to $\dfrac{\pi }{{12}}$

Therefore, $\dfrac{x}{2} = \dfrac{\pi }{{12}}$

$ \Rightarrow x = \dfrac{\pi }{{12}} \times 2 = \dfrac{\pi }{6}$

Placing this value of $x$ in the formula, we get:

$ \Rightarrow {\sin ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{1 - \cos \left( {\dfrac{\pi }{6}} \right)}}{2}$

On simplifying it further, we get:

$ \Rightarrow {\sin ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{1 - \cos {{30}^ \circ }}}{2}$

As we know that the value of $\cos {30^ \circ } = \dfrac{{\sqrt 3 }}{2}$

Therefore, ${\sin ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{1 - \dfrac{{\sqrt 3 }}{2}}}{2}$

$ \Rightarrow {\sin ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{\dfrac{{2 - \sqrt 3 }}{2}}}{2} = \dfrac{{2 - \sqrt 3 }}{2} \times \dfrac{1}{2}$

$ \Rightarrow {\sin ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{2 - \sqrt 3 }}{4}$

Let us take square root of both sides:

$ \Rightarrow \sin \left( {\dfrac{\pi }{{12}}} \right) = \sqrt {\dfrac{{2 - \sqrt 3 }}{4}} $

$ \Rightarrow \sin \left( {\dfrac{\pi }{{12}}} \right) = \dfrac{1}{2}\sqrt {2 - \sqrt 3 } $

Let us find the value for cosine:

The half angle formula for cosine is given as ${\cos ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 + \cos x}}{2}$

Similarly, here also $x = \dfrac{\pi }{6}$

Therefore, ${\cos ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{1 + \cos \left( {\dfrac{\pi }{6}} \right)}}{2}$

On simplifying it further, we get:

$ \Rightarrow {\cos ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{1 + \cos {{30}^ \circ }}}{2}$

As we know that the value of $\cos {30^ \circ } = \dfrac{{\sqrt 3 }}{2}$

Therefore, ${\cos ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{1 + \dfrac{{\sqrt 3 }}{2}}}{2}$

$ \Rightarrow {\cos ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{\dfrac{{2 + \sqrt 3 }}{2}}}{2} = \dfrac{{2 + \sqrt 3 }}{2} \times \dfrac{1}{2}$

$ \Rightarrow {\cos ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{2 + \sqrt 3 }}{4}$

Let us take square root of both sides:

$ \Rightarrow \cos \left( {\dfrac{\pi }{{12}}} \right) = \sqrt {\dfrac{{2 + \sqrt 3 }}{4}} $

$ \Rightarrow \cos \left( {\dfrac{\pi }{{12}}} \right) = \dfrac{1}{2}\sqrt {2 + \sqrt 3 } $

Let us find the half-angle value for tangent:

The half – angle formula for tangent is given as: ${\tan ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \cos x}}{{1 + \cos x}}$

Now as we already know that $x = \dfrac{\pi }{6}$

Therefore, ${\tan ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \cos \left( {\dfrac{\pi }{6}} \right)}}{{1 + \cos \left( {\dfrac{\pi }{6}} \right)}}$

$ \Rightarrow {\tan ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \cos {{30}^ \circ }}}{{1 + \cos {{30}^ \circ }}}$

As we know that the value of $\cos {30^ \circ } = \dfrac{{\sqrt 3 }}{2}$

Therefore, ${\tan ^2}\left( {\dfrac{x}{2}} \right) = \dfrac{{1 - \dfrac{{\sqrt 3 }}{2}}}{{1 + \dfrac{{\sqrt 3 }}{2}}}$

On simplifying it further, we get:

$ \Rightarrow {\tan ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{\dfrac{{2 - \sqrt 3 }}{2}}}{{\dfrac{{2 + \sqrt 3 }}{2}}}$

$ \Rightarrow {\tan ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{2 - \sqrt 3 }}{2} \times \dfrac{2}{{2 + \sqrt 3 }}$

$ \Rightarrow {\tan ^2}\left( {\dfrac{\pi }{{12}}} \right) = \dfrac{{2 - \sqrt 3 }}{{2 + \sqrt 3 }}$

Taking square root on both sides of the equation, we get:

$ \Rightarrow \tan \left( {\dfrac{\pi }{{12}}} \right) = \sqrt {\dfrac{{2 - \sqrt 3 }}{{2 + \sqrt 3 }}} $

**Thus $\sqrt {\dfrac{{2 - \sqrt 3 }}{{2 + \sqrt 3 }}} $ is the required answer.**

**Note:**Trigonometry is a branch of mathematics which deals with triangles. There are many trigonometric formulas that establish a relation between the lengths and angles of respective triangles. In trigonometry, we use a right-angled triangle to find ratios of its different sides and angles such as sine, cosine, tan, and their respective inverse like cosec, sec, and cot.

We may even consider a complete circle and divide it into four quadrants to help us understand our trigonometric identities as so:

When the whole turn around the circle is equal to $2\pi $, while a half circle is equal to $\pi $ . The different quadrants are divided into different angles. All trigonometric identities have positive signs in the first quadrant, while sine has positive values in the second quadrant. Tan has positive values in the third quadrant and cosine has positive values in the fourth quadrant.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Name 10 Living and Non living things class 9 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE